Experimental Research on the Compression Property of Geopolymer Concrete with Molybdenum Tailings as a Building Material - Ming Sun; Yin Fu; Weixin Wang; Youzhi Yang; An Wang (Buildings, 2022)
This paper experimentally studied the effects of different molybdenum tailings (MoT) content, standard curing and 60 °C water curing conditions on the compressive strength of fly ash-based geopolymers at different ages. X-ray diffraction (XRD), scanning electron microscopy/energy dispersive spectrometer (SEM/EDS) and Fourier-transform infrared spectroscopy (FTIR) were applied to investigate the effect of the content of MoT and different curing conditions on the reaction products, microstructure and chemical composition of fly ash-based geopolymers. The results show that MoT content and curing conditions have synergistic effects on the compressive strength of fly ash-based geopolymers. For standard curing, the increase in MoT content is detrimental to the development of compressive strength, and an obvious weak interfacial transition zone between MoT and the gel product is observed in specimen containing 40 wt% MoT; meanwhile, under water curing conditions, the compressive strength of geopolymers first increases and then decreases with the increase in MoT, and the 28-day compressive strength can reach 90.3 MPa when the content of MoT is 10 wt%. The SEM results show that the curing conditions have a great influence on the microstructure of the geopolymer matrix, and the microstructure of the specimens under the water curing conditions is smoother and denser, with fewer pores. EDS analyses show that the gel product constituting the geopolymer matrix is N(C)-A-S-H gel; MoT can participate in the reaction, and the mass ratio of Ca/(Si + Al) of N(C)-A-S-H gel increases with the increase in MoT, resulting in a decrease in compressive strength. In addition, the results of the FTIR confirm that water curing can increase the degree of crosslinks in the gel phase.